Chemical weathering across the western foreland of the Greenland Ice Sheet. (15th January 2019) - Deuerling, Kelly M.; Martin, Jonathan B.; Martin, Ellen E.; Abermann, Jakob; Myreng, Sille Marie; Petersen, Dorthe; Rennermalm, Åsa K.
Abstract: Proglacial streams deliver melt water and chemical weathering products, including nutrients and radiogenic isotopes, from continental ice sheets to the ocean. Weathering products are also delivered to the ocean in non-glacial streams that form following ice sheet retreat and are disconnected from ice sheet meltwater by hydrologic divides. If weathering reactions differ in non-glacial and proglacial stream catchments, the streams could deliver different types and magnitudes of solutes to the ocean, depending on relative discharge volumes. Unlike proglacial streams, however, little is known of non-glacial stream solute compositions or discharge. Here we show specific discharges are similar from a proglacial stream draining the Greenland Ice Sheet (GrIS) with several streams disconnected from the ice sheet. We also evaluate weathering reactions across a 170-km transect in western Greenland that contains one proglacial stream draining the GrIS, and two coastal (ice distal) and three inland (ice proximal) areas with non-glacial streams. Non-glacial streams exhibit solute compositions and offsets between dissolved and bedload Sr isotope ratios that indicate weathering increases toward the coast with exposure age and precipitation. Major element mass balance calculations show weathering reactions shift from predominately carbonic acid weathering of carbonate minerals inland near the ice sheet to predominately sulfuric acid weathering of carbonate minerals near the coast. Strontium concentrations and isotopic ratios of the proglacial stream reflect mixing of at least two subglacial sources and minor in-stream weathering that consumes CO2 . About 5 times less CO2 is consumed per liter in the proglacial than inland non-glacial streams; however, arid conditions inland suggest limited discharge from the ungauged inland streams leads to less total CO2 weathering than proglacial stream. One coastal area consumes less CO2 per liter than the proglacial stream and another coastal area exhibits net CO2 production. These results indicate estimates for glacial foreland solute fluxes and CO2 weathering consumption and production should include estimates from both non-glacial and proglacial streams. Understanding weathering fluxes from these two types of streams will be important for evaluations of past ice sheet retreat and predictions of future solute and CO2 fluxes associated with continued ice sheet retreat.